Associations of ABO blood type and galactose-deficient immunoglobulin A1 with adverse outcomes in patients with IgA nephropathy. Issue 2 (11th October 2019) - Wang, Manliu; Lv, Jicheng; Chen, Pei; Yu, Guizhen; Shi, Sufang; Liu, Lijun; Zhou, Xujie; Xu, Damin; Zhao, Minghui; Zhang, Hong
Abstract: Background: Both ABO blood group antigens and pathogenic immunoglobulin A1 (IgA1) in patients with IgA nephropathy (IgAN) are influenced by modifications of N -acetylgalactosamine and galactose. The purpose of this study was to assess whether ABO blood type is associated with galactose-deficient IgA1 (Gd-IgA1) in the progression of kidney disease in patients with IgAN. Methods: We enrolled 1313 IgAN patients with a median of 44 months follow-up and measured the plasma Gd-IgA1 levels. Multivariate Cox regression models were used to estimate the association between all variables and adverse outcomes. Using the propensity score matching method, 718 IgAN patients with blood type either A or B were selected, and their data were used to assess the association of blood type and Gd-IgA1/serum complement 3 (sC3) with outcomes. Results: We found that the risk of adverse outcomes was significantly higher in patients with blood type A than in those with type B (hazard ratio = 1.82, 95% confidence interval 1.23–2.71; P   =   0.003) after multivariate adjustment. The Gd-IgA1 levels showed trends similar to the multivariate-adjusted event-free curves for the blood types. However, this higher risk of adverse outcomes in type A than in type B patients was no longer significant after the addition of Gd-IgA1/sC3 to the model. Conclusions: IgAN patients with blood type A had a higher risk of adverse outcomes than those with type B, and this risk was associated with Gd-IgA1/sC3. Thus, the ABO blood type may provide a reference for the prognostic factors for individuals with IgAN.